The Northern Atlantic Bluefin Tuna Fisheries: Management and Policy Implications - Trond Bjørndal; Ana Bras\~ao (Fondazione Eni Enrico Mattei (FEEM), 2004)
In this paper, a discrete time, multi-gear and age structured bio-economic model is developed for the Northern Atlantic Bluefin Tuna, which is a paradigmatic example of the difficulties faced in managing highly migratory fish stocks. The 1995 U.N. Fish Stocks Agreement provides guidance as to the sustainable management of straddling and highly migratory fish stocks, maintaining that coastal states and distant water fishing nations should cooperate in the management of these stocks through Regional Fisheries Management Organisations (RFMO). The objective of this paper is to propose alternative management strategies that could be taken into account by the RFMO managing this fishery, and to investigate some of the policy implications.
Keywords: Q22; 330; Bioeconomic model; Bluefin tuna; Optimal management recommendations; Fischerei; Fischereipolitik; Fischereiressourcen; Bioökonomik; Atlantischer Ozean